Green Human Resource Management and Sustainable Employee Performance: The Role of Organizational Commitment - Ridiani Fitriyah; Moh Yudi Mahadianto; Bachrudin Syahroni (Universitas KH. Abdul Chalim Mojokerto, 2026)
In this study, the link between Green Human Resource Management (GHRM), organizational commitment, and sustainable employee performance at PT Arteria Daya Mulia Cirebon. The study is grounded in the view that sustainability-oriented human resource practices do not always influence employee performance directly, but may operate through organizational and psychological mechanisms. Using a quantitative associative design, Partial Least Squares Structural Equation Modelling (PLS-SEM), was used to analyse data gathered from 130 permanent employees. The results demonstrate that both organizational commitment and GHRM have a positive and considerable impact on sustainable employee performance. But the immediate consequence of GHRM on sustainable employee performance is not statistically significant. These results indicate that sustainability-oriented HR practices become more meaningful for long-term employee performance when they strengthen employees’ psychological attachment to the organization. The research adds to the body of knowledge regarding sustainable HRM in manufacturing by showing that organizational commitment has a key role in translating green HR practices into stable and responsible employee performance. Practically, the conclusions imply that manufacturing companies must integrate green-oriented HR policies with managerial efforts to strengthen employee commitment in order to support more sustainable performance outcomes